ANALISIS TINGKAT KESEHATAN BANK SYARIAH DENGAN MENGGUNAKAN METODE RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING DAN CAPITAL) STUDI PADA PT. BANK MUAMALAT IDONESIA TAHUN 2018- 2022 - arini, mega rizqi arini (Jurnal Ilmu Ekonomi dan Bisnis, 2024)
n 2018, Bank Muamalat was rumored to be bankrupt due to the high ratio of nonperforming financing which had an impact on depleting banking capital. This research aims to determine the health level of Bank Muamalat in 2018-2022 using the RGEC method. This type of research uses a quantitative descriptive approach. The data used in this research is secondary data, namely the annual financial reports for 2018-2022. The research results show that the health level of Bank Muamalat Indonesia in 2018 was in the quite healthy category with a final composite score of 62.85% getting a composite rating of 3, in 2019 it was in the quite healthy category with a final composite score of 62.85% getting a composite rating of 3, in 2020 it was in the quite healthy category with a final composite score of 62.58% getting a composite rating of 3, in 2021 it was in the quite healthy category with a final composite score of 68.57% getting a fairly healthy composite rating, and in 2022 it was in the quite healthy category with The final composite score was 68.57%, obtaining a composite rating of 3.